Production frontier methodologies and efficiency as a performance measure in strategic management research. (18th December 2013) - Chen, Chien‐Ming; Delmas, Magali A.; Lieberman, Marvin B.
<x xml:space="preserve">Abstract</x> The measurement of corporate performance is central to strategic management research. A common objective of this research is to identify top performers in an industry and their sources of competitive advantage. Despite this focus on best firms and practices, most researchers utilize statistical methods that identify average effects in a sample, and they assess a single performance dimension while ignoring other relevant dimensions. Emphasis on purely financial measures can overlook the fact that a firm's efficiency in transforming resources has been shown as a major source of competitive advantage. In this article we demonstrate how frontier methodologies, such as Data Envelopment Analysis and the Stochastic Frontier approach, can address these challenges. We provide an illustration based on longitudinal data from U.S. and Japanese automobile producers. Copyright © 2013 John Wiley & Sons, Ltd.